The practice of Yield Management in the chain hotel industry in Morocco: An exploratory study - Imane ELBERTOULI; Salwa BAHYAOUI (Communications of International Proceedings, 2023)
Yield Management (YM), a pricing practice that has become essential in the hotel industry. Over the past two decades, YM has developed thanks to technological advances. However, studies have revealed that this pricing method can arouse negative feelings in customers, affecting their purchasing behavior. The aim of this study is to analyze the impact of YM in chain hotels in Morocco on the perception of Moroccan customers. To this end, a qualitative study was carried out among professionals in the sector to identify the challenges of YM in chain hotels in Morocco and to understand how this practice influences the behavioral reactions of customers.
Keywords: Yield Management; chain hotels in Morocco; customer behavior; perception of unfairness